A CURRICULUM OF INDONESIAN TOURISM VOCATIONAL SCHOOLS - Subijanto Subijanto; Darmawan Sumantri; Burhanuddin Tola; Mariani Mariani (Program Pascasarjana Universitas Negeri Jakarta, 2020)
The purpose of this study is to examine 1) the alignment of the SMK Tourism curriculum with the competency of Catering expertise. according to the competencies needed by the world of work; 2) implementation of learning in schools; 3) implementing industrial work practices; and 4) implementation of competency tests (certification). The background of the research problem is that the Tourism Vocational School graduates have not linked and matched the needs of the world of work. The research method used quantitative and qualitative approaches, while data collection used focus group discussions. The results showed 1) The curriculum of the Vocational High School of Tourism with the competence of Catering expertise in accordance with the competencies needed by the ASEAN tourism workforce based on the Common ASEAN Tourism Curriculum or Level II National Work Competency Standards; 2) learning activities in schools according to the learning implementation plan, teachers master the material and learning methods, where 92.6 percent of teachers have an undergraduate education with at least 20 years of teaching experience; 3) implementation of industrial work practices according to the competence of students' expertise and carried out for 3-6 months; and 4) the implementation of the student competency test (certification) is carried out at the School Professional Certification Institute with cross-school assessors and professional assistants from industry. This study concluded that the competency of the Culinary Vocational School of Tourism expertise is in line with the competencies needed by the ASEAN region of work based on the Level II Indonesian National Work Competency Standards (SKKNI).